Analysis of students’ communicative patterns in a covid-19-moderated learning environment in edo state university Uzairue, Nigeria - Peter Eshioke Egielewa; Obinna Johnkennedy Chukwu (Journal of Management and Science, 2023)
The study aims at analysis of students’ communicative patterns in a Covid-19-Moderated learning environment in Edo State University Uzairue, Nigeria. The study was predicated on the Experimental Learning Theory (ELT). The objectives, amongst others, were to determine the communicative patterns of the students of Edo State University Uzairue in a Covid-19-Moderated Environment, assess whether the Covid-19-moderated learning environment affected the communicative patterns of students of Edo State University Uzairue, as well as, investigate whether the Covid-19-moderated learning environment affected Edo State University Uzairue students’ extra-curricular activities. Survey was adopted as the study design, while questionnaire was used to elicit information from 210 undergraduate students. Findings that the students of Edo State University Uzairue communicative pattern in a Covid-19-moderated learning environment was through virtual (Online), and that despite the inherent challenges enthroned by the Covid-19-moderated learning environment, the students communicated more with friends through the new media platforms. Findings also show that Covid-19-moderated learning environment affected communication among students negatively, and that the implication of the results x-rayed, is that communication amongst students, and between the students and the lecturers, were badly affected by the Covid-19 moderated learning environment, amongst others. Based on the forgoing, the study, amongst others, recommends improvement and introduction of measures that would improve communication amongst the students and the lecturers.